Deficient body structural description contributes to apraxic end-position errors in imitation. (October 2019) - Dafsari, Hormos Salimi; Dovern, Anna; Fink, Gereon R.; Weiss, Peter H.
Abstract: Apraxia is a common cognitive deficit after left hemisphere (LH) stroke. It has been suggested that a disturbed representation of the human body underlies apraxic imitation deficits. Thus, we here tested the hypothesis that a deficient body structural description (BSD), i.e., a deficient representation of a body part's position (relative to a standard human body), contributes to apraxic end-position errors in imitation, while controlling for deficits in the semantic representation of the human body (body image, BI) and naming deficits. A quantitative pointing task to assess putative BSD deficits and an apraxia assessment, including imitation and pantomime tasks, were applied to 27 patients with LH stroke and 19 healthy subjects. While LH stroke patients without apraxia (n=15) did not differ from control subjects in their pointing performance, patients suffering from imitation apraxia (n=10) showed a differential deficit when pointing to body parts of other humans compared to object parts. Voxel-based lesion symptom mapping (VLSM) revealed an association of these differential pointing deficits (indicating a deficient BSD) with lesions in the angular gyrus of the left inferior parietal cortex. This first quantitative group study of BSD deficits in LH stroke patients supports the notion that apraxic end-position errors in imitation are – at least in part – due to a deficient coding of the position of human body parts. Highlights: Deficient body structural description (BSD) impairs pointing to human body parts. We developed a test quantifying BSD deficits in left hemisphere (LH) stroke patients. Apraxic patients showed a specific deficit in pointing to body (vs. object) parts. Body pointing deficits were mainly associated with angular gyrus lesions. Deficient BSD contributes to imitation apraxia in patients with LH stroke.